Living-related liver transplant to treat epithelioid hemangioendothelioma – a case report - Ribeiro Jr, Marcelo A. F. (2005)
Introduction: Epithelioid hemangioendothelioma of liver is a rare, low-grade neoplasm of vascular origin that has an unpredictable malignant potential. It preferentially arises in soft tissues and bones, and seldom in the liver. Biologically, it trends to be multi-focal and often unresectable. Objective: The outcome of a patient submitted to a living-related liver transplant to treat epithelioid hemangioendothelioma of the liver. Case report: The reported case involves a 39-year old female patient with an immense epithelioid hemangioendothelioma of the liver, involving segments III, IV, V, VII, and VIIl. The prognostic to any kind of treatment was considered unfavorable, and the decision of submitting her to a liver transplant was made. It was suggested a living-related liver transplant. The donor was the patient’s 36-year old brother, who donated his right liver lobe (segments V, VI, VII, VIII). The recipient´s original liver was large, presenting very solid consistence and no node evidence. The transplant itself was performed using the conventional living-related liver transplantation technique. The recovery was good, and she was discharged from hospital on the 15th postoperative day using micophenolate mofetil, tacrolimus, and corticoid. Conclusion: Liver transplantation for epithelioid hemangioendothelioma of the liver can be performed with acceptable survival rate. The living related liver transplant opens a great perspective to that group of patients presenting liver tumors and who are unfeasible to wait for an organ on a waiting list.